TELAAH PEMIKIRAN MULYADI KARTANEGARA: DEKONSTRUKSI DAN REKONSTRUKSI KEILMUAN MODERN - Almutawallid (Sulesana: Jurnal Wawasan Keislaman, 2025)
This article examines the thought of Mulyadhi Kartanegara on the deconstruction and reconstruction of modern science through a library research method and philosophical-analytical approach. The study focuses on three main aspects: first, tracing the historical and intellectual background of Mulyadhi Kartanegara; second, analyzing his concept of the Islamization of modern science; and third, exploring his idea of scientific integration. The findings indicate that Mulyadhi Kartanegara is a prominent Indonesian Muslim thinker who offers a profound critique of the dominance of modern Western epistemology. He highlights the inconsistencies of reductionist scientific approaches that neglect spiritual and metaphysical dimensions. His concept of Islamization does not imply a rejection of modernity, but rather an effort to reconstruct an Islamic knowledge system that is integral, contextual, and grounded in tawḥīd. In terms of scientific integration, he emphasizes the need to combine four epistemological approaches: empirical (indrawi), rational (burhani), intuitive (ʿirfani), and textual (bayani). The reconstruction of modern science, in his view, must begin with a fundamental reassessment of its epistemological foundations so that science becomes not merely a tool of technological utility, but a path toward maʿrifah and divine wisdom. Thus, Islam can emerge as an active subject in shaping a holistic and transcendental scientific civilization.